Preservice teachers' beliefs in the context of teaching mathematics to English learners in the United States - Anthony Fernandes; Leslie H. Kahn (Sociedad Española de Investigación en Educación Matemática, 2021)
This study examines the beliefs of fourteen preservice teachers in the Southeast United States about mathematics and language in the context of teaching mathematics to English learners. Qualitative interviews were conducted using survey items as a starting point for the questioning. Speer's (2008) construct of collections of beliefs was used to understand the preservice teachers' belief system and the interaction of beliefs. Three primary beliefs emerged: mathematics is universal, mathematical language, and language barrier. Their belief about mathematics being universal was grounded in their view that mathematics was mostly about symbols and equations. The preservice teachers believed that there was some language in mathematics, though these features were not as pervasive as the symbolic form. Most of them also believed that the English learners were recent immigrants to the country and that English was a barrier for the students in the mathematics classroom. The beliefs interacted in three ways as they responded to the items: dominance, tension, and convergence.